GANDHIAN IDEAS OF GRASSROOT DEVELOPMENT AND INDIAN DEVELOPMENT POLICY IN 21ST CENTURY (SPECIAL REFERENCE OF PANCHAYAT RAJ INSTITUTIONS) - MANDAL, SUDIP (International Journal of Research -GRANTHAALAYAH, 2020)
In the recent times, 'Good Governance' is associated with efficient and effective of administration in a democratic framework and responsiveness of the state and its institutions. The main key elements of 'Good Governance' refer that respect for human rights, equity, rule of law, transparency in public procedure, strong democracy and capacity in public administration.The ideal democracy depends upon the equality of all the purely public opinions. In the same way Gandhian ideas of Panchayat Raj system is a broad concept in independent india and it is a transparency of government in public administration as a part of good governance. It was a concept of diffused grass-roots democracy and process of democratic decentralization. It's a large number of rural people who are directly involved in the field of democratic participation. From ancient times the village has always been regarded as the primary unit in the governance of India. Important govt. policies are implemented through panchayats. The Gram Sabha plays an important role in the whole Panchayat Raj institution in India's democratic system. This is a purely qualitative study. So, Present study is going to focus on the Gandhian point of view Panchayat Raj. This is necessary to development in India 21st century and this conception go ahead powerful in the Nation.